Propagation of electromagnetic waves in hyperbolic metamaterials with epsilon near-zero permittivity - Nguyễn, Phạm Quỳnh Anh; Lê Ngọc Minh (Hue University Journal of Science: Natural Science, 2023)
In this paper, we investigated hyperbolic metamaterials based on a structure containing metallic nanowires embedded in a dielectric matrix with the utility environment theory method. Hyperbolic metamaterials with near-zero permittivity may exist simultaneously in type I and type II. The propagation of transverse electromagnetic waves in these two types of metamaterial was considered. The diverging incident light beam seems to convert into a well-collimated beam and transfers all its energy in the direction perpendicular to the surface of the hyperbolic metamaterial of type I in the region of special values ​​of the incidence angle from –5 to 5°. In the hyperbolic metamaterial of type II, the light wave entirely transmits through the material layers, while the transmittance remains constant in the range of incident angle values ​​from –40 to 40°. The radius of the metal nanowires and the material thickness also affect the characteristics of electromagnetic wave propagation.